Tea leaves moisture prediction using one-port monopole sensor - Ling, J. A.; Then, Yi Lung; Yeow, You Kok; Ahmed, Jubaer; Zaidel, D. N.A. (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper presents the application of using a coaxial monopole sensor for determining and formulating the relationship between the reflection coefficient and the moisture content of tea leaves. A coaxial monopole sensor with operating frequency ranges from 1.35GHz to 1.95GHz was used. The data collections were conducted by using the Vector Network Analyzer. Visual comparison of the results between the actual and predicted gravimetric moisture content are presented. A predictive model is being generated and tested. It is indicated that the monopole sensor has an excellent accuracy of 98.76% and 99.59% in predicting the gravimetric and volumetric moisture content in the sample, respectively. This research has shown that monopole sensor is applicable for the determination of moisture content in tea leaves as an optional sensing technique.